Handle of cotton knitted fabrics : influence of pretreatments - Grancaric, Ana Marija (2009)
Consumers demand for comfort has been permanently rising. In the last twenty years or so a good progress was achieved in this area resulting in more pleasant fabrics handle. It is well know that this complex fabric property depends on fabric constructon, finess of fibers and finishing treatments, although some chemical and most mechanical finishing processes improve it. This paper discusses fabric handle characteristics after some stages of cotton pretreatment. For Such purpose frictional properties of cotton knitted fabrics were evaluated using a new method of measuring fabric coefficient of friction. tested cotton fabrics were alkali and enzymatic scoured, prebleached and bleached in laboratory and in industrial conditions. Degree of plymerization, sewability and fabric friction coefficient were measured and evaluated.